Waiting in Captivity: Slow Borders, Predatory Bureaucracies, and the Necrotemporality of Asylum Deterrence - Martinez, Carlos (Refuge: Canada's Journal on Refugees, 2023)
In recent years, the US government has implemented several bureaucratic changes aimed at stalling the influx of asylum seekers. From the “metering” system initiated under the Obama administration to the Migrant Protection Protocols (MPP) implemented by the Trump administration, these measures have erected a bureaucratic wall against asylum seekers that has kept them captive in Mexican border cities. Drawing on ethnographic fieldwork conducted in Tijuana, Mexico, I examine how these policies have produced deadly conditions for asylum seekers by calibrating time and space in such a way that increases their exposure and vulnerability to highly precarious environments and predatory bureaucracies.